Polyimide hollow fiber gas separation membranes: preparation and the suppression of plasticization in propane/propylene environments - Krol, J.J.; Boerrigter, M.; Koops, G.H.
Asymmetric hollow fiber membranes were prepared using the polyimide Matrimid® 5218. The fibers had an effective top layer thickness of 0.3-0.4 m. The fibers were used in propane and propylene permeation experiments. Whereas the propane permeance remained more or less constant, the propylene permeance increased with feed pressure greater than 1 bar. This indicated that propylene plasticized the membrane material. The fibers were given different heat-treatments in order to investigate the possibilities to suppress the propylene plasticization. This treatment also reduced the permeance considerably, the effect being more pronounced the more intense the heat-treatment was. This was in agreement with scanning electron microscopy studies, which revealed that densification of the fibers occurred due to the heat-treatments. Most important, relatively mild heat-treatments already appeared to be effective in suppressing the propylene plasticization. Since these heat-treated fibers still readily dissolved it is concluded that the plasticization suppression was not due to crosslinking, but to an annealing effect. Due to thermal curing (annealing)at temperatures below the Tg aromatic polyimides tend to form charge transfer complexes, which restrict the polymer chain mobility. Presence of these complexes seems to be responsible for suppression of propylene plasticization.
Keywords: HOLLOW FIBER GAS SEPARATION MEMBRANES; POLYIMIDE; PLASTICIZATION; HEAT-TREATMENTS